Nikah al-Mut'ah min Manzor Ahl al-Sunnah wa al-Jama'ah wa al-Syi'ah al-Imamiyyah - Rohaizan, Baru (2010)
This article tries to forward the debates on the legality of mutaahmarriage which is also known as contract marriage from theperspectives of Ahl al-Sunah wa al-Jamnah and al-Syiah al-Imamiah. In doing so, not only the definition of mutaah marriagegiven by AhI al-Sunah wa al-Jamaah, Shiite and Ibadhiyyah willbe brought to discussions, buldsgarguments forwardpd by eachgroup in supporting their opinion together wtth the academicanalysis on them. In addition, several confusions that appearin relation to this issue will also be tabled. At the end, the mostaccurate andfirm rules; whichwill be decided based on the tabledevidences and analysis will be determined